Environmental nanopollutants : sources, occurrence, analysis and fate - Szpunar, Joanna; Jiménez-Lamana, Javier (Chemistry in the environment series, 2022)
Offering a wide overview of the most recent research on environmental nanopollutants this book gives the reader a full picture of the research on nanoparticles in the environment.